2007
DOI: 10.3923/pjbs.2007.1519.1524
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Campylobacter spp. from Domestic Animals and Poultry in South of Iran

Abstract: A total of 455 domestic animals (cow, horse and camel) and poultry from south of Iran were surveyed for fecal carriage of Campylobacter spp. Out of all collected fecal samples, the highest isolation rate of Campylobacter was recorded among poultry (35%), followed by horse (27%) and cow (21%) while, lowest isolation rate was recorded among camel. Of the 85 Campylobacter strains isolated, 76 were classified as catalase positive Campylobacter. Out of them, high frequency of occurrence was belonged to Campy. jejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
2
15
1
1
Order By: Relevance
“…Parkar et al, (2013) showed similar results for ampicillin (62.50 per cent) and gentamycin (sensitivity patterns as found in the present study. Hundred per cent of the isolates were resistant to azithromycin, ceftazidime, cotrimoxazole and ofloxacin which are in agreement with the reports of Baserisalehi et al, (2007). The resistance of fluoroquinolone group (ciprofloxacin and levofloxacin) and the resistance patterns for clindamycin, erythromycin and gentamicin of the present study are in agreement with the findings of Han et al, (2016).…”
Section: Antibiotic Resistance Profilingsupporting
confidence: 83%
See 1 more Smart Citation
“…Parkar et al, (2013) showed similar results for ampicillin (62.50 per cent) and gentamycin (sensitivity patterns as found in the present study. Hundred per cent of the isolates were resistant to azithromycin, ceftazidime, cotrimoxazole and ofloxacin which are in agreement with the reports of Baserisalehi et al, (2007). The resistance of fluoroquinolone group (ciprofloxacin and levofloxacin) and the resistance patterns for clindamycin, erythromycin and gentamicin of the present study are in agreement with the findings of Han et al, (2016).…”
Section: Antibiotic Resistance Profilingsupporting
confidence: 83%
“…All Campylobacter isolates were examined for their antimicrobial drug susceptibility/resistance pattern by disc diffusion method, as per the procedure described by Baserisalehi et al, (2007) against 33 different antibiotics.…”
Section: Antibiogrammentioning
confidence: 99%
“…In a study on feces samples from camels (Camelus dromedarius), only 2.0% of feces were positive for Campylobacter spp. (Baserisalehi et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…However, the incidence of Campylobacter spp. in the environment largely depends on the climatic conditions of the geographical area (Baserisalehi et al 2007).…”
Section: Introductionmentioning
confidence: 99%